Hospitality: the challenge of the fishing populations that if they transform into suppliers of tourist services - Scorsato, Simone Maria (2006)
In what form does a traditional community, specifically simple people who live along the seashore, offer their guests with regard to hospitality? What are the elements which are inherent to the local culture, and lifestyle offered by the community to travelers? These questions are the base of this study, with observation circumscribed on the Beach of the resting place of Cajaíba (Praia do Pouso da Cajaíba), located on the Juatinga, Paraty Ecological Reserve — south coast of the State of Rio de Janeiro. In Paraty, the most proximate urban center, the touristic activity is consolidated, of which, is a destination known internationally due to its historical center and diverse islands within the region. The motivational factor for the influx of tourism is leisure, principally related to cultural activities and navigation. The option to research the community of the Pouso do Cajaíba was the fact that it possessed certain characteristics — cultural traces inherited from their indigenous and African ancestors, associated techniques and traditional means of sustenance — fishing, hunting and agriculture; the possession of primarily marine access, featuring a kind of cultural insulation, with a lifestyle and customs linked together in a direct relation with the sea; it is a certain isolated form of tourism development featured by urbanization from the regions seashore, but receives an influx of tourism formed by young adventurers of both national and international. They choose this site as a contact with nature and with the local culture. They meet and sleep at the homes offered by the local residents or camp on their backyards. In addition to the presentation and expectations of tourism development as a form or supplementation of income. This survey with intended to discover the effects generated for the development of its ancestral forms of relative to hospitality and overall; the exchange among the tourist and local resident.